Fermentação em estado sólido com bagaço de cevada para produção de enzimas xilanolíticas por penicillium janczewskii e análise do substrato fermentado - Terrasan, César Rafael Fanchini [UNESP]; Carmona, Eleonora Cano [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
In recent decades, increasing interest has been devoted to xylanolytic enzymes due to their potential use in many industrial processes. This study describes the production of xylanase, β-xylosidase and α-Larabinofuranosidase, belonging to the xylanolytic complex, by Penicillium janczewskii using brewer's spent grain as substrate for solid-state fermentation. The optimized conditions for high levels of xylanase, β-xylosidase and α-Larabinofuranosidase production were: 50% initial moisture, which was provided by Vogel’s salt solution, seven days of cultivation at 20-30 °C. Fermentation enriched the bioproduct with some amino acids and did not add mycotoxins to it. The use of brewer's spent grain as substrate for fungal cultivation and enzyme production can both add value to this waste and reduce the production cost of xylanolytic enzymes.
Solid-state fermentation of brewer’s spent grain for xylanolytic enzymes production by penicillium janczewskii and analyses of the fermented substrate
Keywords: Brewer’s spent grain; Enzyme production; Penicillium janczewskii; Solid-state fermentation; Xylanolytic enzymes